2017
DOI: 10.3989/scimar.04482.17a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trampling and digging from shellfishing on <em>Zostera noltei</em> (Zosteraceae) intertidal seagrass beds

Abstract: Summary: Seagrass beds are among the most valuable ecosystems in the world but they are also among the ones most affected by human activities, and they have decreased significantly in recent decades. In many areas, such as in the Basque Country (northern Spain), seagrass beds occupy areas that are also of interest for human activities such as recreation and shellfishing. They may therefore face a number of pressures that cause damage or irreversible states. Taking into account the limited distribution of seagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…Mangrove resources extracted were used for charcoal making, boat making, building poles, and fuel wood [45]. Quinn et al [37] reported similar findings in Brazil and Vietnam, whereas the resources extracted from seagrass included bivalve and bait collection [19,43] and seaweed [22,42] through seaweed farming and fish by using fishnets and traps. The resources obtained from both mangrove forest and seagrass meadows were collected by economically active ages ranging from 26 to 50 years old.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Mangrove resources extracted were used for charcoal making, boat making, building poles, and fuel wood [45]. Quinn et al [37] reported similar findings in Brazil and Vietnam, whereas the resources extracted from seagrass included bivalve and bait collection [19,43] and seaweed [22,42] through seaweed farming and fish by using fishnets and traps. The resources obtained from both mangrove forest and seagrass meadows were collected by economically active ages ranging from 26 to 50 years old.…”
mentioning
confidence: 91%
“…Moreover, assessment done by Watson et al [42] revealed that the global catch of bivalves is approximately 121,000 tonnes per annum with a retail value of m5.5 billion. This increase comes with physical disturbance in seagrass meadows; for example, Garmendia et al [43], Watson et al [42], and Eckrich and Holmquist [44] reported the effect of trampling and digging during bait collection in Zostera noltii (Zosteraceae) and Thalassia testudinum. The present study revealed that substantial numbers of respondents (48%) in all sites studied engage in seaweed farming, and they contribute unknowingly to seagrass degradation.…”
mentioning
confidence: 99%
“…obs. ), although intensive and repeated trampling associated with fishing and digging obviously have stronger and more lasting impacts (Eckrich and Holmquist 2000, Alexandre et al 2005, Skilleter et al 2006, Travaille et al 2015, Garmendia et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Cochón et al 2005, Martin et al 2010, Garmendia et al 2017, in the Bay of Santander the decline was followed by a fast recovery characterized by patches of vegetation alternating in space and time. Today, Z. marina and Z. noltei occupy most of the shallow tidal flats in the Bay of Santander (Ondiviela et al 2015), and the high recovery rate observed suggests that resilient meadows played an important role in this process.…”
Section: Discussionmentioning
confidence: 99%